The Sympathetic Imagination: Recognition, Reciprocity, and Difference - Churcher, Millicent (2016)
In light of the limitations of top-down measures to adequately address the injustices that are suffered by devalued social identities, this thesis examines the sympathetic imagination as a resource for achieving recognition of racial and sexual difference. Adam Smith’s rich and sophisticated account of sympathy in The Theory of Moral Sentiments (1759) is central to this project. Smith claims that our capacity to imaginatively adopt others’ standpoints and to be emotionally affected by their experiences is what binds individuals together as moral agents. Smith acknowledges that the extent to which identify with others’ experiences is often influenced by a lack of understanding, bias and prejudice. Hence, if sympathy is to produce moral behaviour, it must be harnessed to an informed and reflective imaginative exercise. Harmonious social communities in Smith’s view are underpinned by reciprocal exercises of imaginative perspective-taking between individuals, wherein each person strives to grasp the other’s point of view, and to critically scrutinise their response to the other’s feelings. Given the general plausibility of Smith’s naturalistic moral theory, this thesis analyses the massive failures of sympathy that mark contemporary societies, with reference to the concept of the social imaginary. I suggest that the dominant social imaginary of a society has the capacity to systematically undercut fellow-feeling with the experiences of identities that are prevented from shaping prevailing values, norms and meanings, owing to their membership within a marginalised and devalued group. It achieves this by structuring implicit and widely held assumptions about different social identities that exclusively reflect the perspectives of privileged groups, and which render certain possibilities inconceivable or implausible. This research discusses the value and limitations of Smith’s appeal to a form of critical self-regulation as a means of repairing the failures of sympathy engendered by dominant imaginings of sexual and racial difference. This discussion draws attention to the important role played by informal, everyday embodied encounters with others, in addition to institutional structures and bottom up initiatives in facilitating sympathetic identification between privileged and devalued identities